Preparation method of gamma aluminum oxide and gamma aluminum oxide supported palladium catalyst
By using metaaluminate and strong acid and weak alkali salt precipitants in the preparation of γ-Al2O3, gamma alumina with high specific surface area and pore volume was prepared, which solved the complex preparation process of γ-Al2O3 in the prior art and The high cost problem significantly improves the activity and stability of precious metal catalysts.
Patent Information
- Application Number
- CN202311001159.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, the preparation process of γ-Al2O3 as a catalyst support is complex, has high cost and is not conducive to the activity of the supported precious metal catalyst.
By using metaaluminate solution as the aluminum source and driply precipitating with strong acid and weak alkali salt precipitants such as sulfate and sulfite, gamma alumina with high specific surface area, pore volume and special morphology was prepared. , as a support for supporting precious metal catalysts.
The catalytic activity and thermal stability of precious metal catalysts are significantly improved, the amount of precious metals used and catalyst costs are reduced, and the preparation process is simplified, which is the feasibility of industrial production is improved.
Smart Images

Figure BDA0004386468750000111 
Figure HDA0004386468760000011 
Figure HDA0004386468760000012
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, in particular to a method for preparing gamma alumina, the gamma alumina prepared thereby and uses thereof, and also to a gamma alumina-loaded palladium catalyst and uses thereof. Background Art
[0002] The Ministry of Ecology and Environment's "Comprehensive Control Plan for Volatile Organic Compounds in Key Industries" clearly states that volatile organic compounds (hereinafter referred to as VOCs) are important precursors to the formation of PM2.5 and O3. Focusing on industries such as petrochemicals, chemicals, coatings, pharmaceuticals, packaging and printing, and oil storage, transportation and sales, we should promote the comprehensive control of volatile organic compounds safely and efficiently, and implement source replacement projects for raw and auxiliary materials and products.
[0003] Catalytic combustion technology is the last resort for air pollution control. Precious metal catalysts have unsurpassed advantages over other catalysts. Taking the ethylene and methane waste gases emitted from the ethylene silo section and low-temperature methanol washing section of coal chemical industry as an example, ethylene and methane are oxidized to produce carbon dioxide and water under the action of palladium catalysts. Among them, activity and stability are the main performance indicators of palladium catalysts. In the process of ethylene / methane oxidation degradation, the use of palladium catalysts with high activity and good stability can greatly improve purification efficiency, operation stability and economic benefits. Therefore, the manufacture of palladium catalysts with high activity and good stability is the main research direction. In addition to being closely related to the composition and preparation method of the catalyst, the performance of the palladium catalyst is also closely related to the performance and preparation method of the carrier used in the catalyst.
[0004] The preparation method of palladium catalyst mainly includes two processes: preparation of porous carrier (such as alumina) and loading active components onto the carrier. The carrier is generally selected from gamma alumina (γ-Al2O3) with large specific surface area and good thermal stability. γ-Al2O3 has a high specific surface area and can maintain crystal phase stability at 700-800°C, so γ-Al2O3 is generally used as a carrier for VOC oxidation catalyst in industry.
[0005] Chinese patent CN 114433043A discloses "an alumina carrier and its preparation method, silver catalyst and application". This method introduces an alumina precursor and controls the calcination temperature at 1200-1550°C to obtain an alpha alumina (α-Al2O3) carrier for efficient catalytic ethylene epoxidation. However, the α-phase alumina formed by this preparation process is a dense phase, which is 20% smaller in volume than γ-Al2O3. α-Al2O3 also has a lower specific surface area. When used to load a palladium catalyst, it will cause the loaded palladium to agglomerate, thereby reducing the catalytic activity.
[0006] Chinese patent CN 112939045A discloses "a method for preparing ultrafine high-purity γ-alumina". The method first synthesizes alcohol aluminum with metal aluminum and alcohol under the action of a catalyst, then transfers the alcohol aluminum to a vacuum distillation device for refining and purification, dissolves the refined alcohol aluminum in a solvent, adds an appropriate amount of additives during the hydrolysis process, and makes the hydrolysis proceed at a lower temperature. The hydrolysis product is filtered, dried at low temperature, and calcined at high temperature to obtain high-purity γ-Al2O3. The preparation method has a complex process, and the alcohol, solvent, and additives used are mostly flammable, explosive, and toxic organic reagents, which is costly and has low industrial applicability.
[0007] Chinese patent CN 112758968A discloses "alumina precursor and preparation method thereof, submicron alumina and preparation method thereof". This method uses aluminum salt as aluminum source, introduces ammonium carbonate, ammonium bicarbonate, urea or ammonia water as precipitant, adopts two-step precipitation method to prepare alumina precursor and after drying, roasts at 550-1200℃ for 2-6 hours to obtain high-purity submicron alumina. The ammonium carbonate and ammonium bicarbonate used in this method are flammable and explosive substances, while ammonia water and urea are easy to produce nitrogen oxides and have a certain pungent odor, which is not good for environmental protection and health.
[0008] In summary, γ-Al2O3 as a catalyst carrier has an important influence on the catalytic performance of the catalyst. Therefore, it is very necessary to develop a γ-Al2O3 that is conducive to catalyst loading and has a simple preparation process and low cost. Summary of the invention
[0009] In order to make up for the deficiencies in the prior art, an object of the present invention is to provide a method for preparing gamma alumina. By using a specific type of precipitant, the prepared gamma alumina can have a special morphology, better crystallinity, higher specific surface area and pore volume, thereby being more conducive to loading precious metal catalysts and improving the catalytic activity of the catalyst.
[0010] Another object of the present invention is to provide a gamma alumina and use thereof.
[0011] Another object of the present invention is to provide a gamma alumina supported palladium catalyst and use thereof.
[0012] A first aspect of the present invention provides a method for preparing gamma alumina, comprising the following steps:
[0013] S1: using a metaaluminate solution as an aluminum source, and dropping a precipitant solution therein to produce an aluminum oxide precursor; and
[0014] S2: separating the alumina precursor, drying and calcining to obtain the gamma alumina;
[0015] Wherein, the precipitant is one or more of ammonium sulfate, copper sulfate, zinc sulfate, iron sulfate, cobalt sulfate, nickel sulfate, manganese sulfate, ammonium bisulfate, sodium bisulfate, potassium bisulfate, ammonium bisulfite, sodium bisulfite, potassium bisulfite, and ammonium sulfite, and the concentration of the precipitant solution is 10 to 100% of the saturated mass concentration.
[0016] Generally, the acidity of the precipitant determines the speed of precipitation of the alumina precursor (i.e., pseudo-boehmite) and the powder structure of the formed precursor (excessive acidity can easily lead to rapid nucleation and aggregation after precipitation to form a dense structure, while too weak acidity will lead to slow precipitation and small emulsion that cannot be precipitated). In addition, during the precipitation process, cations or anions will also be partially adsorbed on the alumina precursor. Different types of ions are adsorbed on the precursor at different positions, which will also lead to the formation of different microscopic morphologies and exposure of different crystal faces. It can be seen that the acidity and type of the precipitant have an important influence on the preparation and properties of γ-Al2O3, and also affect its catalytic activity when used as a catalyst carrier.
[0017] The precipitant used in the preparation method provided by the present invention is sulfate, sulfite, bisulfate and bisulfite. These salts are strong acid and weak base salts. The solution formed has suitable acidity, which is conducive to the combination of aluminate and hydrogen ions in the precipitant solution to form an alumina precursor by precipitation reaction. Moreover, the precipitant used in the present invention can also make the prepared alumina product have a special microscopic morphology (such as Figure 1 and Figure 2 The nanosheet structure shown in the figure) and high crystallinity can significantly improve its specific surface area, pore volume and other properties, which is beneficial to the loading of precious metal catalysts and can improve the catalytic activity of the loaded catalyst.
[0018] In addition, during the preparation of alumina, a small amount of sulfate and sulfite will be retained on the surface of the prepared alumina. Compared with other anions (such as nitrate, phosphate, hydrogen phosphate, chloride, etc.), the retained small amount of sulfate and sulfite can promote the activity of the catalyst after loading the precious metal.
[0019] In the preparation method provided by the present invention, the saturated mass concentration refers to the mass concentration of the solute (such as precipitant, aluminate, etc.) in the saturated solution state.
[0020] In the preparation method provided by the present invention, the concentration of the precipitant solution can be 10 to 100% of the saturated mass concentration of the precipitant (for example, it can be about 10%, about 20%, about 30%, about 40%, about 50%, about 60%, about 70%, about 80%, about 90%, about 100% or any combination of numerical intervals).
[0021] In some preferred embodiments, the precipitant may be one or more of ammonium sulfate, ammonium bisulfate, ammonium bisulfite, and ammonium sulfite. Ammonium ions can form nitrogen oxides and volatilize during calcination, so they will not affect alumina and the supported catalyst.
[0022] In other preferred embodiments, the precipitant may also be one or more of copper sulfate, zinc sulfate, iron sulfate, cobalt sulfate, nickel sulfate, and manganese sulfate. When the cation of the precipitant is a transition metal element such as iron, cobalt, nickel, copper, zinc, or manganese, it can be doped into alumina. After the noble metal catalyst is loaded, the doped transition metal element can synergize with the noble metal to further improve the activity of the catalyst and expand the application range of the catalyst.
[0023] In some preferred embodiments, the aluminate may be sodium aluminate and / or potassium aluminate.
[0024] In some preferred embodiments, the concentration of the aluminate can be 50-100% of the saturated mass concentration of the aluminate (for example, it can be about 50%, about 60%, about 70%, about 80%, about 90%, about 100% or any combination of numerical intervals).
[0025] In some preferred embodiments, based on every 100 mL of the aluminate solution, the initial dropping speed of the precipitant solution can be 0.2-5 mL / min (for example, it can be about 0.5 mL / min, about 1 mL / min, about 1.5 mL / min, about 2 mL / min, about 2.5 mL / min, about 3 mL / min, about 3.5 mL / min, about 4 mL / min, about 4.5 mL / min, about 5 mL / min, or can be any combination of numerical intervals); when the aluminate solution changes from a transparent solution to a turbid emulsion, the dropping speed can be adjusted to 2-10 mL / min (for example, it can be about 2 mL / min, about 3 mL / min, about 4 mL / min, about 5 mL / min, about 6 mL / min, about 7 mL / min, about 8 mL / min, about 9 mL / min, about 10 mL / min, or can be any combination of numerical intervals). In some more preferred embodiments, the initial dropwise addition speed of the precipitant solution may be 2 to 5 mL / min, and when the aluminate solution changes from a transparent solution to a turbid emulsion, the dropwise addition speed may be adjusted to 6 to 10 mL / min. When the dropwise addition speed of the precipitant solution is too slow, the generated crystals will grow, which may easily lead to the increase of particles. When the dropwise addition speed is too fast, the generated crystals are too small and a large number of fine crystals are formed in a short time, which may easily lead to the final formation of fine irregular particles.
[0026] In some preferred embodiments, when the aluminate solution is stratified after standing (e.g., standing for 10 seconds), the dropwise addition of the precipitant solution is stopped. During the dropwise addition of the precipitant solution, when the pH value of the aluminate solution (alkaline) begins to reach 7, the solution should be frequently allowed to stand during the dropwise addition process to observe whether obvious stratification occurs.
[0027] In some preferred embodiments, depending on the type of the precipitant solution, the total volume of the precipitant solution added dropwise may be 1 / 6 to 1 / 2 of the volume of the aluminate solution.
[0028] In some preferred embodiments, in step S2, the mother liquor remaining after separating the alumina precursor can be recycled as an aluminum source, which can be mixed with a fresh aluminate solution as an aluminum source, or can be used alone as an aluminum source. When the mother liquor is recycled until the pH value is greater than 6, the recycling is stopped.
[0029] In some preferred embodiments, in step S2, the drying conditions may be: a drying temperature of 100 to 150° C. (eg, 110 to 130° C.) and a drying time of 8 to 15 hours (eg, 8 to 12 hours).
[0030] In some preferred embodiments, in step S2, the calcination conditions may be: a calcination temperature of 500-650° C. (eg, 550-600° C.) and a calcination time of 2-8 h (eg, 3-6 h).
[0031] In the preparation method provided by the present invention, the desired material can be obtained through a separation step, such as separation of an alumina precursor, and the separation method can be a common method in the art, including but not limited to natural sedimentation, (normal pressure or vacuum) filtration, centrifugation, etc.
[0032] The second aspect of the present invention provides a gamma alumina, which is prepared by the preparation method described in any one of the above technical solutions.
[0033] In some preferred embodiments, the specific surface area of the gamma alumina may be 200 to 300 m 2 / g (for example, about 200 m 2 / g, about 210m 2 / g, about 220m 2 / g, about 230m 2 / g, about 240m 2 / g, about 250m 2 / g, about 260m 2 / g, about 270m 2 / g, about 280m 2 / g, about 290m 2 / g, about 300m 2 / g or any combination of numerical ranges).
[0034] In some preferred embodiments, the pore volume of the gamma alumina can be 0.2-0.8 mL / g (for example, it can be about 0.2 mL / g, about 0.3 mL / g, about 0.4 mL / g, about 0.5 mL / g, about 0.6 mL / g, about 0.7 mL / g, about 0.8 mL / g or can be any combination of numerical intervals).
[0035] In some preferred embodiments, the gamma alumina is a nanosheet structure with a thickness of no more than 50 nm. In some more preferred embodiments, the gamma alumina has a thickness of 10 to 50 nm.
[0036] The third aspect of the present invention provides the use of the gamma alumina prepared by the preparation method described in any one of the above technical solutions or the gamma alumina described in any one of the above technical solutions as a catalyst carrier.
[0037] As described above, the gamma alumina provided by the present invention or the gamma alumina prepared by the preparation method provided by the present invention has a special microscopic morphology and a high specific surface area and pore volume, and is very suitable for use as a carrier of a supported catalyst, especially a supported precious metal catalyst, and can significantly improve the catalytic activity of the supported precious metal catalyst. Under the same catalytic effect, it can effectively reduce the use of precious metals and reduce the catalyst cost.
[0038] In some preferred embodiments, the catalyst is a noble metal catalyst, including but not limited to one or more of platinum (Pt), rhodium (Rh), palladium (Pd). In some more preferred embodiments, the catalyst is a supported palladium catalyst.
[0039] A fourth aspect of the present invention provides a gamma alumina-supported palladium catalyst, wherein the gamma alumina is gamma alumina prepared by the preparation method described in any one of the above technical solutions or the gamma alumina described in the above technical solution.
[0040] The gamma alumina-supported palladium catalyst provided by the present invention can be prepared by a conventional impregnation method. In some preferred embodiments, the gamma alumina-supported palladium catalyst can be prepared by the following process: the gamma alumina prepared by the preparation method described in any one of the above technical solutions or the gamma alumina described in any one of the above technical solutions is impregnated in a solution containing palladium ions (e.g., a palladium nitrate solution), and the resulting solid is dried at 100 to 130° C. for 8 to 15 hours (e.g., dried at 110 to 120° C. for 10 to 12 hours), and calcined at 200 to 500° C. for 1 to 5 hours (e.g., calcined at 280 to 320° C. for 2 to 3 hours) to obtain the gamma alumina-supported palladium catalyst.
[0041] A fifth aspect of the present invention provides use of the gamma alumina-supported palladium catalyst described in any one of the above technical solutions in the catalytic degradation of ethylene and / or methane.
[0042] The technical solution provided by the present invention has the following advantages:
[0043] (1) The preparation method of gamma alumina provided by the present invention has simple process, mild conditions, wide raw material sources and low cost, and high safety, and is therefore suitable for large-scale industrial production.
[0044] (2) The gamma alumina prepared by the preparation method of the present invention has a nanosheet structure, high crystallinity, and high specific surface area and pore volume, and is very suitable for use as a carrier of a supported precious metal catalyst, and can significantly improve the catalytic activity and thermal stability of the catalyst.
[0045] (3) The gamma alumina-supported palladium catalyst provided by the present invention can be used to catalyze the oxidative degradation of volatile organic compounds such as ethylene and methane, providing a new approach to the prevention and control of volatile organic compound pollution. It is green and environmentally friendly and has very important economic value and social significance. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 This is the SEM image of γ-Al2O3 prepared in Example 1;
[0047] Figure 2 This is the SEM image of γ-Al2O3 prepared in Example 2;
[0048] Figure 3 The SEM image of γ-Al2O3 prepared in Comparative Example 1;
[0049] Figure 4 This is the SEM image of γ-Al2O3 prepared in Comparative Example 2;
[0050] Figure 5XRD comparison spectra of γ-Al2O3 prepared in Example 1-2 and Comparative Example 1-2. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.
[0052] Unless otherwise specified, the raw materials or reagents used in the examples and comparative examples of the present invention are commercially available products.
[0053] The percentages used in the embodiments and comparative examples of the present invention are all mass percentages unless otherwise specified.
[0054] Example 1 Preparation of γ-Al2O3
[0055] (1) preparing 100 mL of a saturated sodium aluminate solution as an aluminum source, and continuously stirring the solution (magnetic stirring speed is 500 rpm);
[0056] (2) preparing 100 mL of saturated ammonium bisulfate solution as a precipitant solution, and continuously stirring the solution (magnetic stirring speed is 500 rpm);
[0057] (3) adding a saturated ammonium bisulfate solution to the continuously stirred saturated sodium aluminate solution at a dropping rate of 4 mL / min until the transparent solution becomes a white turbid emulsion, and adjusting the dropping rate to 8 mL / min;
[0058] (4) When the pH value of the saturated sodium aluminate solution reaches 7, the solution is allowed to stand for 10 seconds every minute during the addition process to observe whether stratification occurs. When obvious stratification occurs, the addition of the saturated ammonium bisulfate solution is stopped;
[0059] (5) subjecting the mixed solution obtained in step (4) to solid-liquid separation to obtain a solid which is an aluminum oxide precursor;
[0060] (6) The alumina precursor obtained in step (5) was dried at 120°C for 10 hours and then calcined at 550°C for 5 hours to obtain γ-Al2O3, the SEM image of which is shown in FIG. Figure 1 The specific surface area and pore volume are shown in Table 1.
[0061] Example 2 Preparation of γ-Al2O3
[0062] (1) preparing 100 mL of a saturated sodium aluminate solution as an aluminum source, and continuously stirring the solution (magnetic stirring speed is 500 rpm);
[0063] (2) preparing 100 mL of saturated ammonium bisulfate solution, diluting it by half as a precipitant solution, and continuously stirring the solution (magnetic stirring speed is 500 rpm);
[0064] (3) adding a saturated ammonium bisulfate solution to the continuously stirred saturated sodium aluminate solution at a dropping rate of 4 mL / min until the transparent solution becomes a white turbid emulsion, and adjusting the dropping rate to 8 mL / min;
[0065] (4) When the pH value of the saturated sodium aluminate solution reaches 7, the solution is allowed to stand for 10 seconds every minute during the addition process to observe whether stratification occurs. When obvious stratification occurs, the addition of the saturated ammonium bisulfate solution is stopped;
[0066] (5) subjecting the mixed solution obtained in step (4) to solid-liquid separation to obtain a solid which is an aluminum oxide precursor;
[0067] (6) The alumina precursor obtained in step (5) was dried at 120°C for 12 hours and then calcined at 550°C for 5 hours to obtain γ-Al2O3, the SEM image of which is shown in FIG. Figure 2 The specific surface area and pore volume are shown in Table 1.
[0068] Example 3 Preparation of γ-Al2O3
[0069] Except for using a saturated copper sulfate solution as the precipitant solution, the remaining steps are the same as those in Example 1 to obtain γ-Al2O3, and the specific surface area and pore volume are shown in Table 1.
[0070] Example 4-8 Preparation of γ-Al2O3
[0071] Except that the precipitant solution is replaced by saturated solutions of zinc sulfate, iron sulfate, cobalt sulfate, nickel sulfate and manganese sulfate, respectively, the remaining steps are the same as those in Example 3 to obtain γ-Al2O3, and the specific surface area and pore volume are shown in Table 1.
[0072] Comparative Example 1 Preparation of γ-Al2O3
[0073] Except for using saturated aluminum nitrate solution as aluminum source and saturated ammonium carbonate solution as precipitant, the remaining steps are the same as those in Example 1 to obtain γ-Al2O3, the SEM image of which is shown in FIG. Figure 3 The specific surface area and pore volume are shown in Table 1.
[0074] Comparative Example 2 Preparation of γ-Al2O3
[0075] Except for using saturated potassium dihydrogen phosphate solution as the precipitant, the remaining steps are the same as those in Example 1 to obtain γ-Al2O3, the SEM image of which is shown in FIG. Figure 4 The specific surface area and pore volume are shown in Table 1.
[0076] Test Example 1 Preparation and Performance Test of γ-Al2O3 Supported Palladium Catalyst
[0077] 1. Preparation of γ-Al2O3 supported palladium catalyst
[0078] (1) Weigh 0.99 g of γ-Al2O3 powder prepared in Example 1;
[0079] (2) Weigh 0.20 g of palladium nitrate solution (Shanghai Jiuling Chemical Co., Ltd., containing 15 wt% palladium) and dilute to 6 mL with deionized water;
[0080] (3) Take 2 mL of the diluted palladium nitrate solution, pour the γ-Al2O3 powder into the solution and stir evenly, heat the solution to 80°C, continue stirring until a paste is formed, place in an oven at 110°C, and dry for 12 hours;
[0081] (4) The dried powder obtained in step (3) is placed in a muffle furnace and heated to 300° C. at a rate of 5° C. / min and calcined for 2 h to obtain a γ-Al 2 O 3 supported palladium catalyst.
[0082] 2. Catalyst performance test
[0083] The γ-Al2O3 supported palladium catalyst prepared in the above steps was used as a test sample to test the performance of the catalyst in oxidative degradation of ethylene and methane.
[0084] The catalyst performance test was carried out in a fixed bed reactor (quartz tube, inner diameter 8 mm), and the gas concentration at the gas outlet was monitored online by an infrared spectrometer (USA, MKS). The initial gas concentration was obtained by passing the gas through an empty quartz tube. The catalyst sample was granulated and screened to obtain 40-60 mesh particles totaling 0.1 g, which were mixed evenly with quartz sand (0.4 g) of the same mesh size. 0.5 g of the mixed sample was placed in a quartz tube, fixed at both ends with quartz wool, and then the catalyst performance test was carried out. The reaction temperatures at which the conversion rates of ethylene or methane oxidation were tested were 10%, 50% and 90%, respectively. The lower the reaction temperature, the better the catalytic performance of the catalyst.
[0085] The atmosphere composition for the ethylene test was as follows: 700 ppm ethylene, 10% oxygen by volume, nitrogen as the balance gas, a total flow rate of 1 liter / minute, and a GHSV of 120,000 h -1 The quartz tube was heated in a tube furnace at a heating rate of 2°C / min to 500°C.
[0086] The atmosphere composition of the methane test is as follows: methane 1000ppm, oxygen volume fraction 10%, nitrogen as the balance gas, total flow rate 1 liter / minute, volume space velocity (GHSV) 120,000h -1 The quartz tube was heated in a tube furnace at a heating rate of 2°C / min to 500°C.
[0087] The test results are shown in Table 2 and Table 3.
[0088] Test Example 2-8 Preparation and Performance Test of γ-Al2O3 Supported Palladium Catalyst
[0089] Except for using the γ-Al2O3 powder prepared in Example 2-8, the remaining steps are the same as those in Test Example 1 to obtain a γ-Al2O3-loaded palladium catalyst.
[0090] The γ-Al2O3 supported palladium catalyst was used as a test sample to test the performance of the catalyst in oxidative degradation of ethylene and methane. The test results are shown in Tables 2 and 3.
[0091] Comparative Test Example 1 Preparation and Performance Test of γ-Al2O3 Supported Palladium Catalyst
[0092] Except for using the γ-Al2O3 powder prepared in Comparative Example 1, the remaining steps are the same as those in Test Example 1 to obtain a γ-Al2O3-loaded palladium catalyst.
[0093] The γ-Al2O3 supported palladium catalyst was used as a test sample to test the performance of the catalyst in oxidative degradation of ethylene and methane. The test results are shown in Tables 2 and 3.
[0094] Comparative Test Example 2 Preparation and Performance Test of γ-Al2O3 Supported Palladium Catalyst
[0095] Except for using the γ-Al2O3 powder prepared in Comparative Example 2, the remaining steps are the same as those in Test Example 1 to obtain a γ-Al2O3-loaded palladium catalyst.
[0096] The γ-Al2O3 supported palladium catalyst was used as a test sample to test the performance of the catalyst in oxidative degradation of ethylene and methane. The test results are shown in Tables 2 and 3.
[0097] Table 1 Specific surface area and pore volume of γ-Al2O3 samples
[0098]
[0099] Table 2 Test results of catalysts for catalytic oxidation of ethylene
[0100] serial number 10% ethylene conversion temperature 50% ethylene conversion temperature 90% ethylene conversion temperature Test Example 1 200℃ 253℃ 270℃ Test Example 2 233℃ 286℃ 311℃ Test Example 3 201℃ 256℃ 272℃ Test Example 4 213℃ 266℃ 281℃ Test Example 5 220℃ 275℃ 290℃ Test Example 6 208℃ 251℃ 262℃ Test Example 7 211℃ 246℃ 275℃ Test Case 8 203℃ 262℃ 285℃ Comparative test example 1 240℃ 296℃ 327℃ Comparative test example 2 250℃ 313℃ 368℃
[0101] Table 3 Catalytic oxidation test results of catalysts for methane
[0102] serial number 10% methane conversion temperature 50% methane conversion temperature 90% methane conversion temperature Test Example 1 303℃ 336℃ 395℃ Test Example 2 333℃ 366℃ 450℃ Test Example 3 308℃ 343℃ 411℃ Test Example 4 310℃ 345℃ 456℃ Test Example 5 332℃ 370℃ 460℃ Test Example 6 301℃ 331℃ 409℃ Test Example 7 296℃ 331℃ 411℃ Test Case 8 317℃ 356℃ 443℃ Comparative test example 1 403℃ 482℃ Above 500℃ Comparative test example 2 Above 500℃ Above 500℃ Above 500℃
[0103] Analysis and summary of the performance of γ-Al2O3 and γ-Al2O3 supported palladium catalysts:
[0104] SEM Characterization:
[0105] like Figure 1-Figure 4 As shown, Examples 1 and 2 use sodium aluminate as the aluminum source and ammonium bisulfate as the precipitant, and the prepared aluminum oxide has a nanosheet structure with a thickness of 10-50 nanometers; Comparative Example 1 uses ammonium bicarbonate as the precipitant and aluminum nitrate as the aluminum source to obtain uniform aluminum oxide nanoparticles with a particle size of about 100 nanometers; Comparative Example 2 uses sodium aluminate as the aluminum source and potassium dihydrogen phosphate as the precipitant to prepare aluminum oxide nanoparticles of about 300 nanometers.
[0106] XRD Characterization:
[0107] like Figure 5 As shown, through XRD characterization analysis, it can be seen that the aluminum oxide prepared in Examples 1 and 2 has better crystallinity and has characteristic peaks of gamma-phase aluminum oxide crystal form, and the characteristic peaks appear, and are very obvious; the gamma-phase aluminum oxide formed in Comparative Example 1 has poor crystallinity compared with the example; the aluminum oxide formed in Comparative Example 2 has no characteristic peaks, and the peaks between 20 and 40° indicate that it is amorphous aluminum oxide.
[0108] In summary, the gamma alumina prepared in Examples 1 and 2 using aluminate as the aluminum source and ammonium bisulfate as the precipitant has good crystallinity, while the alumina prepared in Comparative Examples 1 and 2 cannot reach the corresponding level.
[0109] Specific surface area and pore volume characterization:
[0110] As shown in Table 1, judging by the specific surface area and pore volume, the alumina prepared in Examples 1 to 8 have both high specific surface area and pore volume, providing abundant places for loading the active components of the catalyst, which is beneficial to the dispersion of the active components and the improvement of the activity. The alumina prepared in Comparative Examples 1 and 2 cannot reach the corresponding specific surface area and pore volume levels.
[0111] Comparison of ethylene catalytic performance:
[0112] According to the results in Table 2, compared with the catalysts in Comparative Test Example 1 and Comparative Test Example 2, the catalysts in Test Examples 1-8 have better catalytic performance, and the 10% ethylene conversion temperature (T 10 ), 50% ethylene conversion temperature (T 50 ) and 90% ethylene conversion temperature (T 90 ) were significantly reduced.
[0113] Comparison of Methane Catalytic Performance:
[0114] According to the results in Table 3, compared with the catalysts in Comparative Test Example 1 and Comparative Test Example 2, the catalysts in Test Examples 1-8 have better catalytic performance, and the 10% methane conversion temperature (T10 ), 50% methane conversion temperature (T 50 ) and 90% methane conversion temperature (T 90 ) are significantly reduced. The conversion temperature of the catalyst in Test Example 2 for catalyzing methane oxidation is above 500°C, which means that the catalyst has basically no catalytic activity.
[0115] Unless otherwise defined, the terms used in the present invention have the meanings commonly understood by those skilled in the art.
[0116] The embodiments described in the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention. Those skilled in the art may make various other substitutions, changes and improvements within the scope of the present invention. Therefore, the present invention is not limited to the above embodiments, but is only limited by the claims.
Claims
1. A method for preparing gamma alumina, characterized in that: The following steps are involved: S1: using aluminate solution as an aluminum source, and adding a precipitant solution dropwise therein to produce an aluminum oxide precursor; as well as S2: separating the alumina precursor, drying and calcining to obtain the gamma alumina; Wherein, the precipitant is one or more of ammonium sulfate, copper sulfate, zinc sulfate, iron sulfate, cobalt sulfate, nickel sulfate, manganese sulfate, ammonium bisulfate, sodium bisulfate, potassium bisulfate, ammonium bisulfite, sodium bisulfite, potassium bisulfite, and ammonium sulfite, and the concentration of the precipitant solution is 10 to 100% of the saturated mass concentration.
2. The preparation method according to claim 1, characterized in that: The aluminate is sodium aluminate and / or potassium aluminate; Preferably, the concentration of the metaaluminate solution is 50-100% of the saturation mass concentration.
3. The preparation method according to claim 1 or 2, characterized in that: Based on every 100 mL of the aluminate solution, the initial dropping speed of the precipitant solution is 0.2 to 5 mL / min. When the aluminate solution changes from a transparent solution to a turbid emulsion, the dropping speed is adjusted to 2 to 10 mL / min.
4. The preparation method according to any one of claims 1 to 3, characterized in that When the aluminate solution separates into layers after standing, the dropwise addition of the precipitant solution is stopped.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The drying conditions are as follows: drying temperature is 100-150° C., and drying time is 8-15 hours.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The calcination conditions are as follows: the calcination temperature is 500-650° C. and the calcination time is 2-8 hours.
7. A gamma alumina prepared by the preparation method according to any one of claims 1 to 6; preferably, the gamma alumina has a specific surface area of 200 to 300 m 2 / g; and / or The pore volume of the gamma alumina is 0.2 to 0.8 mL / g; and / or The gamma alumina is a nanosheet structure with a thickness of no more than 50 nm.
8. Use of the gamma alumina prepared by the preparation method according to any one of claims 1 to 6 or the gamma alumina according to claim 7 as a catalyst carrier; preferably, the catalyst is a precious metal catalyst, more preferably one or more of platinum, rhodium and palladium.
9. A gamma alumina supported palladium catalyst, characterized in that The gamma alumina is the gamma alumina prepared by the preparation method according to any one of claims 1 to 6 or the gamma alumina according to claim 7; Preferably, the gamma alumina-supported palladium catalyst is prepared by the following process: the gamma alumina prepared by the preparation method described in any one of claims 1 to 6 or the gamma alumina described in claim 7 is impregnated in a solution containing palladium ions (preferably a palladium nitrate solution), the resulting solid is dried at 100 to 130° C. for 8 to 15 h, and calcined at 200 to 500° C. for 1 to 5 h to obtain the gamma alumina-supported palladium catalyst.
10. Use of the gamma alumina supported palladium catalyst according to claim 9 in the catalytic degradation of ethylene and / or methane.
Citation Information
Patent Citations
Alumina precursor and preparation method thereof, and submicron alumina and preparation method thereof
CN112758968A
Preparation method of superfine high-purity gamma-aluminum oxide
CN112939045A
Alumina carrier, preparation method thereof, silver catalyst and application
CN114433043A